Non-alcoholic fatty liver disease and pregnancy complications among Sri Lankan women: A cross sectional analytical study. - Rasika Pradeep Herath; Shirom R Siriwardana; Chanil D Ekanayake; Vikum Abeysekara; Sajith U A Kodithuwakku; Himali P Herath (PLoS ONE, 2019)
Background Non-alcoholic fatty liver disease (NAFLD) is the commonest cause of liver disease worldwide and is the hepatic manifestation of metabolic syndrome. Effects of NAFLD on pregnancy is still unclear with few studies showing an association to gestational diabetes and pre-eclampsia. We aimed to describe the association between the NAFLD and pregnancy complications. This is the first study, to our knowledge, in a South Asian population. Method A cross sectional analytical study was done in Teaching Hospital, Ragama, Sri Lanka. Women carrying a singleton pregnancy, admitted for delivery were assessed for NAFLD with liver ultrasound scan. Data were extracted from interviewer administered questionnaire and antenatal and inpatient records. Pregnancy complications and labour outcomes were compared between the women with NAFLD and women without NAFLD (non-NAFLD). Results Out of the 573 women who participated, 18.2% (n = 104) were found to have NAFLD. Out of them, 58 (55.8%), 32(30.8%), and 14(13.5%) had fatty liver grade 1,2 and 3 respectively. Women with NAFLD were 2 times more likely to develop gestational hypertension and pre-eclampsia compared to the women in the non-NAFLD group, after adjusting for BMI, age and Hyperglycaemia in pregnancy [Adjusted OR 2.09, (95% CI 1.07-4.10)]. There was no association between the grade of steatosis and a composite outcome of gestational hypertension and pre-eclampsia, within the NAFLD group. Composite outcome of gestational diabetes mellitus and diabetes in pregnancy diagnosed during pregnancy was a significant complication in the NAFLD group compared to non-NAFLD group in the bivariate analysis (27.2% vs 17.7%; p<0.05), but the significance disappeared after adjusting for confounders. The current study did not demonstrate a significant association between NAFLD with preterm labour, caesarean section rate, low birth weight, and Apgar score of the baby. Conclusion Women with NAFLD had a 2-fold higher risk of developing gestational hypertension and pre-eclampsia during pregnancy compared to women without NAFLD, after controlling for other confounding variables.